The Unbearable Opportunity Costs of the Political Science PhD: Evidence and Lessons from Canada. - Jamal, Bianca; Berdahl, Loleen; Malloy, Jonathan; Young, Lisa (Canadian Journal of Political Science / Revue Canadienne de Science Politique)
Limited academic career prospects are pushing PhD graduates in political science and other disciplines to nonacademic careers. Understanding the mismatch between student and supervisor perceptions of doctoral career training is a starting point for suggesting program reforms. This research note examines the perceptions of PhD students and supervisors on doctoral career training. We compare results from two surveys of English-speaking Canadian universities on doctoral political science programs; one surveys PhD students and the other surveys supervisors. These survey results suggest that 1) students are more aware of the limited academic job market and interested in nonacademic careers than supervisors realize; 2) supervisors are unaware of the sunk costs PhD students face; 3) supervisors and students have different preferences for change in doctoral programs; and 4) students overestimate supervisors' confidence in preparing them for nonacademic careers. Changes in program design can better meet student needs in these PhD programs.